A coated modified positive electrode material and its preparation method and application

By using a composite material of fluorine-terminated MXene and cobalt aluminum oxide to coat the lithium-ion battery positive electrode material matrix, the problem of lattice collapse during rapid cycle is solved, and its performance is significantly improved.

CN118888737BActive Publication Date: 2025-02-07ZHUJI PAWA NEW ENERGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411375253.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-02-07
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Existing lithium-ion battery positive electrode materials are prone to lattice collapse and collapse during rapid circulation, affecting their discharge specific capacity, cycle stability and rate performance.

Method used

A composite material of fluorine-end group MXene and cobalt aluminum oxide is used as the coating material, and the surface of the LiNixCoyMnzO2 matrix is ​​coated, and the coated modified cathode material is prepared by hydrothermal reaction and ball milling.

Benefits of technology

The structure and interface stability of the positive electrode material are enhanced, the metal dissolution and side reactions are inhibited, and the discharge specific capacity, cycle stability and rate performance are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118888737B_ABST
    Figure CN118888737B_ABST
Patent Text Reader

Abstract

The invention belongs to the field of lithium ion battery materials and discloses a coated modified positive electrode material, comprising a positive electrode material matrix and a coating material coated on at least a part of the surface of the positive electrode material matrix; the positive electrode material matrix is ​​LiNi x Co y Mn z O2, 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z=1; the coating material is a composite material of fluorine-terminated MXene and cobalt aluminum oxide. The fluorine end group in the coating material, as a high electronegative element, can enhance the structural and interfacial stability of the positive electrode material and inhibit the metal dissolution and side reactions of the positive electrode material; the cobalt element in the cobalt aluminum oxide can improve the conductivity and electron transfer efficiency of the positive electrode material, and the aluminum element further enhances the structural stability of the positive electrode material; the combination of the two improves the discharge specific capacity, cycle stability and rate performance of the battery. In addition, the preparation method and application of the above-mentioned coated modified positive electrode material are also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of lithium ion battery materials, and specifically relates to the coating modification of lithium ion battery positive electrode materials, and especially to coating materials, coated modified positive electrode materials, and batteries. Background Art

[0002] In recent years, with the rapid expansion of the electric vehicle market, the demand for high-performance lithium-ion batteries with high energy density and long cycle life has increased dramatically. The booming electric vehicle industry has not only promoted the innovation of battery technology, but also accelerated the research and development of lithium-ion batteries with higher energy density, longer service life and higher safety.

[0003] Lithium battery cathode materials are the key to determining the performance of lithium-ion batteries, and their conductivity and structural stability have a great impact on battery performance. Transition metal oxides have always been a hot research object in electrochemical energy storage, electrochemical sensing, adsorption, catalysis, etc. due to their potential electrochemical activity, excellent electron transfer capacity, and simple availability. Compared with precious metals such as Au and Pt, doping transition metals represented by Cu, Fe, Ni, Co, etc. in cathode materials can achieve the effect of reducing costs and increasing efficiency. However, during the redox reaction of transition metals and their derivatives, due to changes in the ion valence state, their lattices will change with the changes in the valence state. During the multiple rapid and uninterrupted cycles of the battery, the lattice is prone to irreversible collapse and disintegration, affecting the discharge capacity, cycle stability and rate performance of the cathode material. Summary of the invention

[0004] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a coated and modified positive electrode material; in the second aspect, the present invention provides a method for preparing the coated and modified positive electrode material; in the third aspect, the present invention provides a battery.

[0005] In a first aspect, the present invention provides a coated modified positive electrode material, comprising a positive electrode material matrix and a coating material coated on at least a portion of the surface of the positive electrode material matrix; the positive electrode material matrix is ​​LiNi x Co y Mn z O2, 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z=1; the coating material is a composite material of fluorine-terminated MXene and cobalt aluminum oxide.

[0006] In a second aspect, the present invention provides a method for preparing a coated modified positive electrode material, comprising the following steps:

[0007] Step 1, adding titanium aluminum carbide (Ti3AlC2) to a hydrofluoric acid solution to react for a period of time to obtain a fluorine-terminated MXene suspension; mixing a mixed aqueous solution of cobalt nitrate and aluminum nitrate and a precipitant, reacting for a period of time, and separating the obtained precipitate, i.e., cobalt aluminum hydroxide;

[0008] Step 2, washing the cobalt aluminum hydroxide with a fluorine-terminated MXene suspension multiple times to obtain an intermediate product, and then transferring the intermediate product to a reactor for hydrothermal reaction to obtain a crude coating material precursor;

[0009] Step 3, drying and ball-milling the crude coating material precursor to obtain the coating material precursor;

[0010] Step 4: Prepare the coating material precursor, Ni x Co y Mn z The (OH)2 precursor and the lithium salt are mixed and ball-milled to obtain a mixed powder; the mixed powder is calcined in an inert atmosphere to obtain a coated modified positive electrode material; wherein 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z=1.

[0011] Preferably, the total concentration of aluminum and fluorine in the fluorine-terminated MXene suspension is 0.1-0.4 mol / L; the molar concentration ratio of aluminum and fluorine in the fluorine-terminated MXene suspension is 1:1-20.

[0012] Preferably, the molar ratio of cobalt ions to aluminum ions in the mixed aqueous solution of cobalt nitrate and aluminum nitrate is 1:0.1-5.

[0013] Preferably, the precipitant is prepared from a mixed solution of sodium hydroxide and sodium carbonate; the volume ratio concentration of sodium hydroxide and sodium carbonate in the precipitant is 1:0.1-5.

[0014] Preferably, in step 1, the pH value of the reaction system is maintained at 8-12 when the mixed aqueous solution of cobalt nitrate and aluminum nitrate reacts with the precipitant.

[0015] Preferably, after step 1 and before step 2, the method further comprises the step of aging the cobalt aluminum hydroxide, specifically, aging the mixture of the mixed aqueous solution of cobalt nitrate and aluminum nitrate and the precipitant at 60-80° C. for 12-24 hours.

[0016] Preferably, in step 2, the cobalt aluminum hydroxide is washed 1 to 10 times with a fluorine-terminated MXene suspension; when washing 1 g of cobalt aluminum hydroxide, the amount of the fluorine-terminated MXene suspension used for each washing is 0.01 to 5 L.

[0017] Preferably, in step 2, the hydrothermal temperature is 100-220° C., and the hydrothermal time is 5-48 h.

[0018] Preferably, in step 3, the drying temperature is 60-80° C. and the drying time is 8-18 hours.

[0019] Preferably, in step 4, the molar ratio of lithium in the precursor and lithium salt is 1:0.8-4.

[0020] Preferably, the mass ratio of the precursor to the coating material is 1:0.01%~5%.

[0021] Preferably, in step 4, the calcination temperature is 500-1000° C. and the calcination time is 12-48 hours.

[0022] In a third aspect, a battery comprises the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned method for preparing the positive electrode material.

[0023] Compared with the prior art, the present invention has the following obvious beneficial effects:

[0024] (1) The fluorine end group in the coating material, as a highly electronegative element, can enhance the structural and interfacial stability of the positive electrode material and inhibit the metal dissolution and side reactions of the positive electrode material; the cobalt element in the cobalt-aluminum hydrotalcite can improve the conductivity and electron transfer efficiency of the positive electrode material, and the aluminum element further enhances the structural stability of the positive electrode material; the positive electrode material matrix and the coating material cooperate with each other, so that the positive electrode material has a higher discharge specific capacity, better cycle stability and better rate performance.

[0025] (2) The process for preparing the coating material provided by the present invention is simple, easy to operate, and conducive to production and industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is the XRD pattern of the fluorine-terminated MXene material obtained in step 1 of Example 1;

[0027] Figure 2 This is the infrared spectrum of the fluorine-terminated MXene material obtained in step 1 of Example 1;

[0028] Figure 3 This is a SEM image of the fluorine-terminated MXene material prepared in step 1 of Example 1;

[0029] Figure 4 This is a SEM image of the cobalt aluminum hydroxide obtained in step 4 of Example 1;

[0030] Figure 5 This is a SEM image of the coating material precursor obtained in step 5 of Example 1;

[0031] Figure 6 This is a SEM image of the positive electrode material prepared in Example 1;

[0032] Figure 7 is the XRD pattern of the positive electrode material prepared in this Example 1;

[0033] Figure 8 This is the SEM image of the positive electrode material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0034] The present invention provides the following specific technical solutions.

[0035] In a first aspect, the present invention provides a coated modified positive electrode material, comprising a positive electrode material matrix and a coating material coated on at least a portion of the surface of the positive electrode material matrix; the positive electrode material matrix is ​​LiNi x Co y Mn z O2, 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z=1; the coating material is a composite material of fluorine-terminated MXene and cobalt aluminum oxide.

[0036] The fluorine end group in the coating material, as a highly electronegative element, can enhance the structural and interfacial stability of the positive electrode material and inhibit the metal dissolution and side reactions of the positive electrode material; the cobalt element in the cobalt-aluminum hydrotalcite can improve the conductivity and electron transfer efficiency of the positive electrode material, and the aluminum element further enhances the structural stability of the positive electrode material; the positive electrode material matrix and the coating material cooperate with each other, so that the positive electrode material has a higher discharge specific capacity, better cycle stability and better rate performance.

[0037] In a second aspect, the present invention provides a method for preparing a coated modified positive electrode material, comprising the following steps:

[0038] Step 1, adding titanium aluminum carbide (Ti3AlC2) to a hydrofluoric acid solution to react for a period of time to obtain a fluorine-terminated MXene suspension; mixing a mixed aqueous solution of cobalt nitrate and aluminum nitrate and a precipitant, reacting for a period of time, and separating the obtained precipitate, i.e., cobalt aluminum hydroxide;

[0039] Step 2, washing the cobalt aluminum hydroxide with a fluorine-terminated MXene suspension multiple times to obtain an intermediate product, and then transferring the intermediate product to a reactor for hydrothermal reaction to obtain a crude coating material precursor;

[0040] Step 3, drying and ball-milling the crude coating material precursor to obtain the coating material precursor;

[0041] Step 4: Prepare the coating material precursor, Ni x Co y Mn zThe (OH)2 precursor and the lithium salt are mixed and ball-milled to obtain a mixed powder; the mixed powder is calcined in an inert atmosphere to obtain a coated modified positive electrode material; wherein 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z=1.

[0042] The fluorine-terminated MXene material can be coated on the surface of the cobalt aluminum hydroxide by washing the cobalt aluminum hydroxide with the fluorine-terminated MXene suspension multiple times, and the bonding strength between the fluorine-terminated MXene material and the cobalt aluminum hydroxide is further enhanced by hydrothermal reaction. Then, the precursor of the positive electrode material, the precursor of the coating material and the lithium source are ball-milled, mixed and roasted to obtain the positive electrode material. The process for preparing the coating material provided by the present invention is simple, easy to control, and conducive to promotion and marketization.

[0043] Preferably, the total concentration of aluminum and fluorine in the fluorine-terminated MXene suspension is 0.1-0.4 mol / L; the molar concentration ratio of aluminum and fluorine in the fluorine-terminated MXene suspension is 1:1-20.

[0044] Excess hydrofluoric acid when preparing MXene materials can increase the reaction rate and yield and ensure the conductivity of the MXene material.

[0045] Preferably, the molar ratio of cobalt ions to aluminum ions in the mixed aqueous solution of cobalt nitrate and aluminum nitrate is 1:0.1-5.

[0046] The inventors have found through research that the content of cobalt ions and aluminum ions in the metal salt solution affects the electrochemical properties of the positive electrode material. If there are more cobalt ions in the metal salt solution, the radius of the cobalt ions is larger, and they usually have a larger interlayer spacing and a stronger metal-oxygen bond, which is beneficial to improving the initial capacity of the positive electrode material; if there are more aluminum ions in the metal salt solution, the aluminum ions have a high charge and a smaller radius, resulting in a smaller interlayer spacing, a more compact and stable structure, which is beneficial to improving the cycle retention rate of the positive electrode material; if the ratio of cobalt ions and aluminum ions in the metal salt solution is similar, the cobalt and aluminum ions are evenly distributed in the structure of the hydrotalcite, forming a balanced interlayer structure, so that the initial capacity and cycle retention rate of the positive electrode material are at a higher level.

[0047] Preferably, the precipitant is prepared from a mixed solution of sodium hydroxide and sodium carbonate; the volume ratio concentration of sodium hydroxide and sodium carbonate in the precipitant is 1:0.1-5.

[0048] In the preparation process of cobalt aluminum hydrotalcite, the combined use of sodium hydroxide and sodium carbonate can control the pH value of the reaction, the precipitation rate, the type and distribution of interlayer anions, thereby affecting the structure and properties of the final material. Reasonable adjustment of the ratio of the two and the reaction conditions can obtain cobalt aluminum hydrotalcite with ideal layered structure and physicochemical properties.

[0049] Preferably, when the mixed aqueous solution of cobalt nitrate and aluminum nitrate and the precipitant are mixed, the precipitant is added dropwise to the mixed aqueous solution of cobalt nitrate and aluminum nitrate until the pH value of the reaction system is 8 to 12, and the addition of the precipitant is stopped.

[0050] Preferably, after step 1 and before step 2, the method further comprises the step of aging the cobalt aluminum hydroxide, specifically, aging the mixture of the mixed aqueous solution of cobalt nitrate and aluminum nitrate and the precipitant at 60-80° C. for 12-24 hours.

[0051] Preferably, in step 2, the cobalt aluminum hydroxide is washed 1 to 10 times with a fluorine-terminated MXene suspension; when washing 1 g of cobalt aluminum hydroxide, the amount of the fluorine-terminated MXene suspension used for each washing is 0.01 to 5 L.

[0052] During the washing process, it can be observed that the cobalt aluminum hydroxide gradually turns black, which means that the MXene material is coated on the surface of the hydrotalcite material.

[0053] Preferably, in step 2, the hydrothermal temperature is 100-220° C., and the hydrothermal time is 5-48 h.

[0054] Preferably, in step 3, the drying temperature is 60-80° C. and the drying time is 8-18 hours.

[0055] Preferably, in step 4, the molar ratio of lithium in the precursor and lithium salt is 1:0.8-4.

[0056] Preferably, the mass ratio of the precursor to the coating material is 1:0.01%~5%.

[0057] Preferably, the calcination temperature is 500-1000° C. and the calcination time is 12-48 hours.

[0058] Preferably, the lithium salt is a lithium salt commonly used in preparing positive electrode materials. In a specific embodiment of the present invention, the lithium salt used is lithium hydroxide.

[0059] Preferably, the gas providing the inert atmosphere is a common inert gas. In a specific embodiment of the present invention, argon gas is used.

[0060] In a fifth aspect, a battery comprises the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned method for preparing the positive electrode material.

[0061] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0062] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0063] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0064] Embodiment 1:

[0065] A method for preparing a positive electrode material comprises the following steps:

[0066] Step 1: Add 2 g of Ti3AlC2 precursor to 50 ml of 40% hydrofluoric acid and react at 35 °C for 24 hours to generate a fluorine-terminated MXene suspension.

[0067] Step 2: Filter the fluorine-terminated MXene suspension, and wash the obtained solid particles with ionized water for multiple ultrasonic washes to remove hydrofluoric acid and other by-products until the pH value of the washing solution is stabilized in the neutral range. Add the washed solid particles to 50 ml of deionized water to prepare a slurry.

[0068] Step 3, weighing 0.2 mol of cobalt nitrate and 0.1 mol of aluminum nitrate, dissolving them in 30 ml of deionized water, and stirring them evenly to obtain a metal salt solution; mixing a sodium hydroxide solution and a sodium carbonate solution to prepare a precipitant, wherein the concentration of sodium hydroxide in the precipitant is 0.5 mol / L, and the concentration of sodium carbonate is 0.5 mol / L.

[0069] Step 4, slowly drop the precipitant into the metal salt solution and stir, and control the reaction temperature to 25°C (room temperature), and stop dropping the precipitant when the pH value of the reaction system reaches 10; then age the obtained slurry at 70°C for 18 hours and filter it, and the obtained precipitate is cobalt aluminum hydroxide.

[0070] Step 5, divide the slurry prepared in step 2 into 5 equal parts, wash 1 g of the cobalt aluminum hydroxide prepared in step 4 5 times, then dry the washed cobalt aluminum hydroxide at 70°C for 13 hours, and then disperse the dried product by ball milling to obtain the coating material precursor.

[0071] Step 6: Take 0.05g of coating material precursor, 3g of Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor material and 1.423 g of lithium hydroxide were mixed evenly, and then the mixed powder was poured into a ball mill and ball milled at a speed of 700 r / min for 2 h.

[0072] Step 7, transferring the ball-milled mixed powder to a high-temperature furnace and calcining it at 750° C. for 30 hours under an argon atmosphere to obtain the positive electrode material.

[0073] Figure 1 This is the XRD pattern of the fluorine-terminated MXene material obtained in step 1 of Example 1. Figure 1 It can be proved that the material prepared in step 1 is a fluorine-terminated MXene material.

[0074] Figure 2 This is the infrared spectrum of the fluorine-terminated MXene material obtained in step 1 of Example 1. Figure 2 It can be demonstrated that the material obtained in step 1 contains fluorine end groups.

[0075] Figure 3 This is a SEM image of the fluorine-terminated MXene material obtained in step 1 of Example 1. Figure 3 It can be seen that the fluorine-terminated MXene material prepared in step 1 has a multilayer structure.

[0076] Figure 4 is a SEM image of the cobalt aluminum hydroxide obtained in step 4 of Example 1. Figure 4 It can be seen that the prepared cobalt aluminum hydroxide has no agglomeration phenomenon and has fine particles.

[0077] Figure 5 is a SEM image of the coating material precursor obtained in step 5 of Example 1. Figure 5 It can be seen that the coated material has many wrinkles and fine particles, which indirectly proves the successful composite of fluorine-terminated MXene and cobalt aluminum hydroxide.

[0078] Figure 6 is a SEM image of the positive electrode material obtained in Example 1. Figure 6 It can be seen that there are fine particles on the surface of the positive electrode material, which can indirectly prove that the coating is successful.

[0079] Figure 7 is the XRD pattern of the positive electrode material prepared in this embodiment 1, Figure 7 It can be proved that the matrix of the positive electrode material prepared by the present invention is Ni 0.9 Co 0.05 Mn 0.05 O2, but the amount of coating material (fluorine-terminated MXene and cobalt aluminum oxide) used is too small, and the characteristic peaks are not obvious.

[0080] Comparative Example 1:

[0081] A method for preparing a positive electrode material comprises the following steps:

[0082] Step 1, weighing 0.2 mol of cobalt nitrate and 0.1 mol of aluminum nitrate, dissolving them in 30 ml of deionized water, and stirring them evenly to obtain a metal salt solution; mixing a sodium hydroxide solution and a sodium carbonate solution to prepare a precipitant, wherein the concentration of sodium hydroxide in the precipitant is 0.5 mol / L, and the concentration of sodium carbonate is 0.5 mol / L.

[0083] Step 2, slowly drop the precipitant into the metal salt solution and stir, and control the reaction temperature to 25°C (room temperature), and stop dropping the precipitant when the pH value of the reaction system reaches 10; then age the obtained slurry at 70°C for 18 hours and filter it, and the obtained precipitate is cobalt aluminum hydroxide.

[0084] Step 3, washing 1 g of the cobalt aluminum hydroxide obtained in step 4 with deionized water 5 times, using 10 ml of deionized water for each washing; then drying the washed cobalt aluminum hydroxide at 70° C. for 13 h, and then ball-milling and dispersing the dried product to obtain cobalt aluminum hydroxide.

[0085] Step 4, take 0.05g of cobalt aluminum hydroxide, 3g of Ni 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor material and 1.423 g of lithium hydroxide were mixed evenly, and then the mixed powder was poured into a ball mill and ball milled at a speed of 700 r / min for 2 h.

[0086] Step 5, transferring the ball-milled mixed powder to a high-temperature furnace and calcining it at 750° C. for 30 hours under an argon atmosphere to obtain the positive electrode material.

[0087] Comparative Example 2:

[0088] A method for preparing a positive electrode material comprises the following steps:

[0089] Step 1: Add 2 g of Ti3AlC2 precursor to 50 ml of 40% hydrofluoric acid and react at 35 °C for 24 hours to generate a fluorine-terminated MXene suspension.

[0090] Step 2: Filter the fluorine-terminated MXene suspension, and wash the obtained solid particles with ionized water for multiple ultrasonic washes to remove hydrofluoric acid and other by-products until the pH value of the washing solution is stabilized in the neutral range. Then, dry the fluorine-terminated MXene at 70°C for 13h, and then disperse the dried product by ball milling to obtain the MXene-F coated material.

[0091] Step 3, 0.05g MXene-F coating material, 3g Ni 0.9 Co 0.05 Mn 0.05The (OH)2 precursor material and 1.423 g of lithium hydroxide were mixed evenly, and then the mixed powder was poured into a ball mill and ball milled at a speed of 700 r / min for 2 h.

[0092] Step 4, transferring the ball-milled mixed powder to a high-temperature furnace and calcining it at 750° C. for 30 hours under an argon atmosphere to obtain the positive electrode material.

[0093] Comparative Example 3:

[0094] A method for preparing a positive electrode material comprises the following steps:

[0095] Step 1, take 3gNi 0.9 Co 0.05 Mn 0.05 The (OH)2 precursor material and 1.1384 g of lithium hydroxide were mixed evenly, and then the mixed powder was poured into a ball mill and ball milled at a speed of 700 r / min for 2 h.

[0096] Step 7, transferring the ball-milled mixed powder to a high-temperature furnace and calcining it at 750° C. for 30 hours under an argon atmosphere to obtain the positive electrode material.

[0097] Figure 8 is the SEM image of the positive electrode material prepared in Comparative Example 3, Figure 8 It can be seen that the surface of the positive electrode material is smooth; by contrast Figure 6 and Figure 8 , which can further prove that the preparation method provided by the present invention can successfully coat the coating material on the surface of the positive electrode material matrix.

[0098] Embodiment 2:

[0099] A method for preparing a positive electrode material comprises the following steps:

[0100] Step 1: Add 1 g of Ti3AlC2 precursor to 50 ml of 5% hydrofluoric acid and react at 35 °C for 24 hours to generate a fluorine-terminated MXene suspension.

[0101] Step 2: Filter the fluorine-terminated MXene suspension, and wash the obtained solid particles with ionized water for multiple ultrasonic washes to remove hydrofluoric acid and other by-products until the pH value of the washing solution is stabilized in the neutral range. Add the washed solid particles to 50 ml of deionized water to prepare a slurry.

[0102] Step 3, weighing 0.2 mol of cobalt nitrate and 0.02 mol of aluminum nitrate, dissolving them in 30 ml of deionized water, and stirring them evenly to obtain a metal salt solution; mixing a sodium hydroxide solution and a sodium carbonate solution to prepare a precipitant, wherein the concentration of sodium hydroxide in the precipitant is 0.5 mol / L, and the concentration of sodium carbonate is 0.05 mol / L.

[0103] Step 4, slowly drop the precipitant into the metal salt solution and stir, and control the reaction temperature to 25°C (room temperature), and stop dropping the precipitant when the pH value of the reaction system reaches 8; then age the obtained slurry at 60°C for 12 hours and filter it, and the obtained precipitate is cobalt aluminum hydroxide.

[0104] Step 5, using the slurry prepared in step 2 to wash 1 g of the cobalt aluminum hydroxide prepared in step 4 once, and then drying the washed cobalt aluminum hydroxide at 60° C. for 8 hours, and then ball-milling and dispersing the dried product to obtain a coating material precursor.

[0105] Step 6: Take 0.005g of coating material precursor, 3g of Ni 0.7 Co 0.2 Mn 0.1 The (OH)2 precursor material and 1.138 g of lithium hydroxide were mixed evenly, and then the mixed powder was poured into a ball mill and ball milled at a speed of 200 r / min for 1 h.

[0106] Step 7, transferring the ball-milled mixed powder to a high-temperature furnace and calcining it at 500° C. for 12 h in an argon atmosphere to obtain the positive electrode material.

[0107] Embodiment 3:

[0108] A method for preparing a positive electrode material comprises the following steps:

[0109] Step 1: Add 1 g of Ti3AlC2 precursor to 50 ml of 40% hydrofluoric acid and react at 35 °C for 24 hours to generate fluorine-terminated MXene.

[0110] Step 2: Use ionized water to ultrasonically wash the fluorine-terminated MXene multiple times to remove hydrofluoric acid and other by-products until the pH value of the washing solution is stabilized in the neutral range, and the washed solid particles are added to 50 ml of deionized water to prepare a slurry.

[0111] Step 3, weighing 0.2 mol of cobalt nitrate and 1 mol of aluminum nitrate, dissolving them in 500 ml of deionized water, and stirring them evenly to obtain a metal salt solution; mixing a sodium hydroxide solution and a sodium carbonate solution to prepare a precipitant, wherein the concentration of sodium hydroxide in the precipitant is 0.5 mol / L, and the concentration of sodium carbonate is 2.5 mol / L.

[0112] Step 4, slowly drop the precipitant into the metal salt solution and stir, and control the reaction temperature to 25°C (room temperature), and stop dropping the precipitant when the pH value of the reaction system reaches 12; then age the obtained slurry at 80°C for 24 hours and filter it, and the obtained precipitate is cobalt aluminum hydroxide.

[0113] Step 5, divide the slurry prepared in step 2 into 5 equal parts, wash 1 g of the cobalt aluminum hydroxide prepared in step 4 5 times, then dry the washed cobalt aluminum hydroxide at 80°C for 18 hours, and then disperse the dried product by ball milling to obtain the coating material precursor.

[0114] Step 6: Take 0.5g of coating material precursor and 3g of Ni 0.8 Co 0.1 Mn 0.1 The (OH)2 precursor material and 3.104 g of lithium hydroxide were mixed evenly, and then the mixed powder was poured into a ball mill and ball milled at a speed of 200 r / min for 6 hours.

[0115] Step 7, transferring the ball-milled mixed powder to a high-temperature furnace and calcining it at 1200° C. for 48 hours under an argon atmosphere to obtain the positive electrode material.

[0116] The positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were assembled into batteries in the following manner:

[0117] The positive electrode materials, conductive agents (conductive carbon black) and adhesives (polyvinylidene fluoride) prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were mixed in a mass ratio of 80:10:10, an appropriate amount of NMP solvent was added, and the mixture was stirred evenly to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil current collector, and then the coated aluminum foil was dried at 70°C to remove the NMP solvent. The dried electrode was compacted using a tablet press at a pressure of 100 to 200 MPa. The compacted electrode material was punched into a positive electrode sheet with a diameter of 14 mm using a punching die, and a polypropylene (PP) or polyethylene (PE) diaphragm was used to cut into circular sheets of the same size as the electrode sheet. 1M LiPF6 was dissolved in a mixed solvent of EC / DMC (ethylene carbonate / dimethyl carbonate), an appropriate amount of additives (such as FEC (fluoroethylene carbonate)) was added as an electrolyte, and a lithium sheet with a diameter of 14 mm was used as a negative electrode sheet. The positive electrode sheet, negative electrode sheet and electrolyte are assembled into a button battery, placed in an aging cabinet for aging, and the current is controlled to 0.05C for the first charge and discharge of the battery, charging to 4.2V and discharging to 2.5V.

[0118] Batteries assembled from the positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3 were tested under the following test conditions.

[0119] Capacity test: At 25°C, the battery was charged and discharged for multiple cycles at a current density of 0.1C, and the charge and discharge capacity was recorded.

[0120] Cycle performance test: At a current density of 1C or higher, the battery is subjected to a long-term charge and discharge cycle test to evaluate the cycle stability of the battery.

[0121] Rate performance test: Perform charge and discharge tests at different rates (such as 0.1C, 0.5C) to evaluate the rate performance of the battery.

[0122] The test data is shown in Table 1.

[0123] Table 1 Performance test data of batteries assembled from positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 3

[0124]

[0125] It can be seen from Table 1 that the battery assembled from the positive electrode material prepared in Example 1 has a higher initial specific capacity, better rate performance and cycle stability. Compared with the positive electrode materials prepared in Comparative Example 1 (hydrotalcite coating), Comparative Example 2 (fluorine-terminated MXene coating) and Comparative Example 3 (not coated), Example 1 can significantly improve the initial specific capacity, rate performance and cycle stability of the positive electrode material by coating the positive electrode material with hydrotalcite and fluorine-terminated MXene coating materials.

[0126] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a coated modified positive electrode material, characterized in that: The steps include: Step 1, adding titanium aluminum carbide Ti3AlC2 to a hydrofluoric acid solution to react for a period of time to obtain a fluorine-terminated MXene suspension; mixing a mixed aqueous solution of cobalt nitrate and aluminum nitrate and a precipitant, reacting for a period of time, and separating the obtained precipitate, i.e., cobalt aluminum hydroxide; Step 2, washing the cobalt aluminum hydroxide with a fluorine-terminated MXene suspension multiple times to obtain an intermediate product, and then transferring the intermediate product to a reactor for hydrothermal reaction to obtain a crude coating material precursor; Step 3, drying and ball-milling the crude coating material precursor to obtain the coating material precursor; Step 4: Prepare the coating material precursor, Ni x Co y Mn z The (OH)2 precursor and the lithium salt are mixed and ball-milled to obtain a mixed powder; the mixed powder is calcined in an inert atmosphere to obtain a coated modified positive electrode material; wherein 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z=1.

2. The method for preparing the coating material according to claim 1, characterized in that: The total concentration of aluminum and fluorine in the fluorine-terminated MXene suspension is 0.1~0.4 mol / L; the molar concentration ratio of aluminum and fluorine in the fluorine-terminated MXene suspension is 1:1~200; the molar ratio of cobalt ions and aluminum ions in the mixed aqueous solution of cobalt nitrate and aluminum nitrate is 1:0.1~5.

3. The method for preparing the coating material according to claim 1 or 2, characterized in that: In step 1, when the mixed aqueous solution of cobalt nitrate and aluminum nitrate and the precipitant are mixed, the precipitant is added dropwise to the mixed aqueous solution of cobalt nitrate and aluminum nitrate until the pH value of the reaction system is 8-12, and the addition of the precipitant is stopped.

4. The method for preparing the coating material according to claim 1, characterized in that: In step 2, the cobalt aluminum hydroxide is washed 1 to 10 times with a fluorine-terminated MXene suspension; when washing 1 g of cobalt aluminum hydroxide, the amount of the fluorine-terminated MXene suspension used for each washing is 0.01 to 5 L.

5. The method for preparing the coating material according to claim 1, characterized in that: In step 2, the temperature of the hydrothermal reaction is 100-220° C., and the time of the hydrothermal reaction is 5-48 hours.

6. The method for preparing the coating material according to claim 1, characterized in that: After step 1 and before step 2, the method further includes aging the cobalt aluminum hydroxide, specifically, aging a mixture of a mixed aqueous solution of cobalt nitrate and aluminum nitrate and a precipitant at 60-80° C. for 12-24 hours.

7. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 4, the molar ratio of lithium in the precursor and the lithium salt is 1:0.8~4; the mass ratio of the precursor and the coating material is 1:0.01%~5%; the calcination temperature is 500~1000°C; and the calcination time is 12~48h.

8. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 1, the precipitant is prepared from a mixed solution of sodium hydroxide and sodium carbonate; the concentration of sodium hydroxide and sodium carbonate in each liter of the precipitant is 1:0.1-5.

9. A coated modified positive electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 8; the positive electrode material comprises a positive electrode material matrix and a coating material coated on at least part of the surface of the positive electrode material matrix; the positive electrode material matrix is ​​LiNi x Co y Mn z O2, 0.7≤x<1, 0<y≤0.2, 0<z≤0.3, x+y+z=1; the coating material is a composite material of fluorine-terminated MXene and cobalt aluminum oxide.

10. A battery, characterized in that: A positive electrode material prepared by the method for preparing the positive electrode material according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Composite metallic-oxide-cladded lithium nickel cobalt manganese oxide anode material and preparation method thereof

    CN102244260A

  • Cobalt-based positive electrode material with composite coating layer, preparation method of cobalt-based positive electrode material and lithium ion battery

    CN117352736A